2012
DOI: 10.1124/mol.112.079640
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pharmacological Characterization of Multiple Allosteric Binding Sites on the Free Fatty Acid 1 Receptor

Abstract: Activation of FFA1 (GPR40), a member of G protein-coupling receptor family A, is mediated by medium-and long-chain fatty acids and leads to amplification of glucose-stimulated insulin secretion, suggesting a potential role for free fatty acid 1 (FFA1) as a target for type 2 diabetes. It was assumed previously that there is a single binding site for fatty acids and synthetic FFA1 agonists. However, using members of two chemical series of partial and full agonists that have been identified, radioligand binding i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
172
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(179 citation statements)
references
References 51 publications
(52 reference statements)
6
172
0
1
Order By: Relevance
“…5 In fact, studies using radiolabeled ligands have indicated that FFA1 possesses at least three distinct binding sites that recognize structurally closely related ligands and that each site is able to allosterically modulate ligand function at the others. 6 The recently published crystal structure of FFA1 in complex with 1 lent further support to the concept of multiple FFA1 binding sites, revealing several potential binding sites in addition to the site of 1. 7 Most importantly from a drug development standpoint, the specific binding site an FFA1 agonist interacts with may influence the ligand's downstream signaling outcomes, 2c and thus may have clear implications for the ultimate therapeutic efficacy of any developed FFA1 agonists.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…5 In fact, studies using radiolabeled ligands have indicated that FFA1 possesses at least three distinct binding sites that recognize structurally closely related ligands and that each site is able to allosterically modulate ligand function at the others. 6 The recently published crystal structure of FFA1 in complex with 1 lent further support to the concept of multiple FFA1 binding sites, revealing several potential binding sites in addition to the site of 1. 7 Most importantly from a drug development standpoint, the specific binding site an FFA1 agonist interacts with may influence the ligand's downstream signaling outcomes, 2c and thus may have clear implications for the ultimate therapeutic efficacy of any developed FFA1 agonists.…”
Section: Introductionmentioning
confidence: 91%
“…It is therefore possible that at least some aspects of the discrepancy between potency and affinity observed for certain chemical series of FFA1 agonists could be related to binding kinetics. A third factor that may contribute to the discrepancy is the apparent presence of the multiple binding sites in FFA1, [5][6] implying the possibility of partial or lack of overlap with 4. In line with these observations, lauric acid was found to behave as an allosteric compound incompetent to fully displace 4, in contrast to the synthetic agonists that all behaved as fully competitive with 4, indicating at least partially overlapping binding sites.…”
Section: Characterization Of 4 As An Ffa1 Tracermentioning
confidence: 99%
See 1 more Smart Citation
“…Récem-ment, une autre série d'agonistes de GPR40, incluant AMG-837 et ses dérivés (Amgen), a été proposée [18,19]. Certaines de ces molécules agissent comme des modulateurs allostériques et potentialisent les effets insulinotropes des acides gras [52]. Des agonistes de GPR119 sont également en cours de développement clinique pour le traitement du DT2 [53].…”
Section: Utilisation Thérapeutique Des Récepteurs Membranaires Des Acunclassified
“…Such has been the case in developing selective allosteric agonists for individual subtypes of both muscarinic [37] and metabotropic glutamate receptors [38]. Finally, since a GPCR presumably has only one orthosteric binding site, yet may have multiple allosteric sites as evidenced by detailed studies of for example muscarinic acetylcholine [37] and FFA1 receptors [39], developing allosteric ligands also represents a viable strategy in situations where the orthosteric site is simply not amenable to drug development.…”
Section: Pharmacological Advantages Of Allos-teric Gpcr Ligandsmentioning
confidence: 99%